Mass Spectrometry - Based Comprehensive Proteomic Analyses of Biological Samples: from Wood Frogs Liver Tissues to Cancer-Derived Extracellular Vesicles - Li, Yingxi (Université d'Ottawa | University of Ottawa, 2024)
Proteomic studies have rapidly advanced in recent years, revolutionizing the field of biology and biomedical research. Proteomics is the large-scale study of proteins, and it provides an understanding of protein structures, compositions, functions, protein-protein interactions, and their cellular activities. In this thesis, MS-based proteomic approaches were applied to two different biological systems: liver tissues from wood frogs and breast cancer (BC)-derived extracellular vesicles. Chapter 2 focuses on exploring the molecular adaptations of freeze-tolerant wood frogs. Wood frogs have excellent freeze tolerance and can survive environmental challenges such as limited water availability, low oxygen levels, and extremely low temperatures that can lead to whole-body freezing. A comprehensive proteomic analysis was conducted on frog liver tissue exposed to anoxia, dehydration, or freezing using a label-free LC-MS/MS proteomic approach. The quantitative analysis identified 87, 118, and 86 proteins that were significantly upregulated in the dehydrated, anoxic, and frozen groups, respectively, indicating their potential protective roles. The study also confirmed the upregulation of three enzymes: GST, ALDOA, and SORD. These enzymes exhibited significantly higher specific activity in the livers of the frozen and anoxic groups compared to the controls. Chapter 2 suggests that GST, ALDOA, and SORD may be involved in the freeze tolerance mechanism by contributing to cellular detoxification and energy metabolism. Chapter 3 focuses on identifying potential biomarkers from BC-derived EVs. BC is one of the most diagnosed malignancies among women and the second leading cause of cancer-related death in North America. Small membrane-derived extracellular vesicles (sEVs) have considerable potential as diagnostic agents and can be detected at the earliest stage of cancers. We aim to study global proteome in small EVs to find biomarkers for BC diagnosis, and three BC cell lines were examined (two cancerous and one non-cancerous cell line). Three types of proteomics approaches were conducted: quantitative, phosphoproteomics, and proteomics acetylation analysis. Our quantitative proteomics analyses and previously reported data strongly suggest that 11 identified enzymes may be potential candidates as biomarkers for the diagnosis of BC. Among the phosphoproteins, we validated four enzymes associated with cancer and present only in sEVs isolated from cancerous cell lines: ACLY, PFKM, SIRT1, and SIRT6. The protein acetylation study revealed that ALDOA, PGK1 and ENO showed a significantly higher specific enzymatic activity in cancerous cell lines in comparison to the non-cancerous cell line. Thus, proteomic studies reveal that sEVs contain enzymes that could be interesting potential candidates for early BC diagnostics. Future validation of enzymes using both cancer cell lines and blood from BC patients remains to be determined.
Keywords: Proteomics; Extracellular Vesicles; Wood Frogs; Breast Cancer; Enzyme Biomarkers